Metallomic Analysis of Macrophages Infected with Histoplasma capsulatum Reveals a Fundamental Role for Zn in Host Defenses - Winters, Michael S. (2010)
The fungal pathogen Histoplasma capsulatum evades the innate and adaptive immune responses and thrives within resting macrophages (Mφ). Cytokines that induce antimicrobial activity such as granulocyte macrophage-colony stimulating factor (GM-CSF) inhibit H. capsulatum growth in Mφ. Conversely, interleukin 4 (IL-4) inhibits the killing of intracellular pathogens. Using inductively coupled plasma mass spectrometry, we examined alterations in metal homeostasis of murine H. capsulatum-infected Mφ infected that were exposed to activating cytokines. Restriction of iron (Fe(2+/3+)) and zinc (Zn(2+)) was observed in infected, GM-CSF-treated Mφ compared to infected controls. IL-4 reversed the anti-fungal activity of GM-CSF-activated Mφ and was associated with increased intracellular Zn(2+). Chelation of Zn(2+) inhibited yeast replication both in the absence and presence of Mφ. Treatment of cells with GM-CSF altered the host Zn(2+) binding species profile. These results establish that Zn(2+) deprivation may be a host defense mechanism utilized by Mφ.